The Impact of COVID-19 Surges in 2019–2021 on Patient-Reported Outcome Measures After Spine Surgery at an Academic Tertiary Referral Center in Taiwan: A Retrospective Observational Cohort Study - Lin, Yu-Hsien; Wang, Jun-Sing; Wang, Wen-Chien; Lin, Yu-Tsung; Wu, Yun-Che; Chen, Kun-Hui; Pan, Chien-Chou; Chin, Ning-Chien; Shih, Cheng-Min; Lee, Cheng-Hung (Frontiers in Surgery, 2022)
Aim: Limited data are available on the impact of the coronavirus disease 2019 (COVID-19) pandemic on patient-reported outcome measures (PROMs) in patients who underwent spine surgery. In this study, we aimed to investigate the associations between the COVID-19 outbreak in Taiwan (May 2021) and PROMs in patients who underwent spine surgery. Method: We retrospectively identified patients who underwent spine surgery during identical defined 6-week time-intervals (May 16 to June 30) in 2019, 2020, and 2021. PROMs, including visual analog scale (VAS) score for pain, Oswestry disability index (ODI), and EuroQol-5D (EQ-5D), were investigated before surgical intervention and at a 1-month follow-up. Relevant clinical information was collected from the electronic medical records of patients. Linear regression analysis was used to examine the association between the pandemic in 2021 (vs. 2019/2020) and the PROMs after adjusting for age, sex, and relevant clinical variables. Results: The number of patients who underwent spine surgery at our hospital during the identical defined 6-week time-intervals in 2019, 2020, and 2021 was 77, 70, and 48, respectively. The surgical intervention significantly improved VAS, ODI, and EQ-5D of the patients (one month after surgery vs. before surgery, all p < 0.001) in all three study periods. However, there was a significant between-group difference in change from baseline in VAS (p = 0.002) and EQ-5D (p = 0.010). The decrease in VAS and increase in EQ-5D after surgery in 2021 were not as much as those in 2019 and 2020. The associations between the pandemic in 2021 (vs. 2019/2020) and changes in VAS (β coefficient 1.239; 95% confidence interval [CI] 0.355 to 2.124; p = 0.006) and EQ-5D (β coefficient, -0.095; 95% CI, -0.155 to -0.035; p = 0.002) after spine surgery were independent of relevant clinical factors. Conclusion: There was less improvement in short-term PROMs (VAS and EQ-5D) after spine surgery during the COVID-19 pandemic. Assessment of PROMs in surgical patients during a pandemic may be clinically relevant, and psychological support in this condition might help improve patients’ outcomes.